Identification of Proteins and Genes Expressed by Methylophaga thiooxydans During Growth on Dimethylsulfide and Their Presence in Other Members of the Genus - Kröber, Eileen; Schäfer, Hendrik (Frontiers in Microbiology, 2019)
Dimethylsulfide is a volatile organic sulfur compound that provides the largest input of biogenic sulfur from the oceans to the atmosphere, and thence back to land, constituting an important link in the global sulfur cycle. Microorganisms degrading DMS affect fluxes of DMS in the environment, but the underlying metabolic pathways are still poorly understood. Methylophaga thiooxydans is a marine methylotrophic bacterium capable of growth on DMS as sole source of carbon and energy. Using proteomics and transcriptomics we identified genes expressed during growth on dimethylsulfide and methanol to refine our knowledge of the metabolic pathways that are involved in DMS and methanol degradation in this strain. Amongst the most highly expressed genes on DMS were the two methanethiol oxidases driving the oxidation of this reactive and toxic intermediate of DMS metabolism. Growth on DMS also increased expression of the enzymes of the tetrahydrofolate linked pathway of formaldehyde oxidation, in addition to the tetrahydromethanopterin linked pathway. Key enzymes of the inorganic sulfur oxidation pathway included flavocytochrome c sulfide dehydrogenase, sulfide quinone oxidoreductase, and persulfide dioxygenases. A sulP permease was also expressed during growth on DMS. Proteomics and transcriptomics also identified a number of highly expressed proteins and gene products whose function is currently not understood. As the identity of some enzymes of organic and inorganic sulfur metabolism previously detected in Methylophaga has not been characterised at the genetic level yet, highly expressed uncharacterised genes provide new targets for further biochemical and genetic analysis. A pan-genome analysis of six available Methylophaga genomes showed that only two of the six investigated strains, M. thiooxydans and M. sulfidovorans have the gene encoding methanethiol oxidase, suggesting that growth on methylated sulfur compounds of M. aminisulfidivorans is likely to involve different enzymes and metabolic intermediates. Hence, the pathways of DMS-utilization and subsequent C1 and sulfur oxidation are not conserved across Methylophaga isolates that degrade methylated sulfur compounds.